Georgia : Technical Assessment Report-Tax Administration Diagnostic Assessment Tool-Performance Assessment Report. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Technical Assistance paper discusses key findings of the assessment of the tax administration system in Georgia. Viewed overall, the Georgia Revenue Service is making good progress in implementing modern tax administration practices. Particularly evident is the innovative use of new technology in modernizing current operations. International good practices are already in place in a number of areas. For others, implementation of good practices is progressing; in some cases it has yet to be adopted. Many of the weaknesses identified in this assessment can be rectified relatively quickly, and in some areas, small changes can make a big difference to outcomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet